Impactos da modernização agrícola para os agricultores familiares da mesorregião sudoeste do Paraná - Alberton, Viviane Balazote (2019)
Family Farming is an important social and economic segment in Brazil. Nevertheless, though the Agricultural Revolution of the 1960s turned the country into a world-respected agricultural juggernaut, it has also deepened the stat e of social exclusion of the poorest family farming producers, not to mention the associated environmental damage. Taking into account the agricultural modernization brought about by such a revolution, this study aimed at investigating in which manner Family Farming producers from the Southwest mesoregion of the Parana State , assisted by National Rural Housing Program( PNHR), were able to resist and thus remain in their properties. This study was a field research, of descriptive feature and approached using a qualitative manner. We interviewed 88 families distributed among the municipalities of the aforementioned region. The results obtained showed that small producers have not had sufficient conditions to escape poverty, properties possess few technological instrument, low productivity and presented, for the most part, no productive diversification. In spite of this reality, the farmers survived on the field, overcoming difficult situations, using knowledge and experiences acquired throughout their lives, are resilient and show strong bonds with the rural environment, especially the properties in which they live. Besides, it has been observed the importance of technical assistance available to the farmers, who even without an economic focus, still guarantee good standard of living to the families. The results obtained in this study show the need of more structure and sustainable policies, which could bring more opportunities and alternatives for survival to the most decapitalized population, given the role of this segment not only for the economy but for the maintaining of the culture of food production through family farming in the southwest mesoregion of the state of Parana